1997
DOI: 10.1161/01.cir.96.7.2128
|View full text |Cite
|
Sign up to set email alerts
|

The Münster Heart Study (PROCAM)

Abstract: The increase in mortality at low levels of total and LDL cholesterol among middle-aged men in the Münster Heart Study is explained by an increase in smoking-related cancer deaths among smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(42 citation statements)
references
References 69 publications
5
36
0
1
Order By: Relevance
“…Study design and recruitment of participants Recruitment to the PROCAM Study 10,11 was started in 1979.…”
Section: Methodsmentioning
confidence: 99%
“…Study design and recruitment of participants Recruitment to the PROCAM Study 10,11 was started in 1979.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of the lipoprotein and apolipoprotein ratios, which frequently are associated with changes in cardiovascular risk, 6 showed that the LDL/HDL cholesterol ratios and apoA-I/B ratios in control subjects were both in the normal range …”
Section: Clinical Characteristics Of Participating Subjectsmentioning
confidence: 99%
“…2 All carriers are heterozygous for the mutation 3 and share a lipoprotein disorder characterized by very low plasma levels of HDL cholesterol with moderate hypertriglyceridemia, 4 a condition that has been associated with a high risk of premature coronary heart disease in numerous epidemiological studies. 5,6 The clinical status of the apoA-I M carriers has been generally associated with a reduced cardiovascular risk. This conclusion was essentially based on historical data pertaining to the whole Limone sul Garda population and, in particular, to a prior study investigating the clinical conditions of the apoA-I M carriers.…”
mentioning
confidence: 99%
“…It was shown in multiple large prospective studies of cardiovascular risk factors that reduced plasma levels of HDL-cholesterol (HDL-C) are associated with an increased risk of coronary artery disease (CAD) (Castelli et al 1986;Cullen et al 1997;Di Angelantonio et al 2009;Gordon et al 1977;Sharrett et al 2001). Multiple biological functions of HDL have been identified, whereby HDL may exert antiatherogenic effects (Annema and von Eckardstein 2013;Barter et al 2004;Mineo et al 2006;Rader 2006;, e.g., HDL from healthy subjects has been shown to directly promote endothelial antiapoptotic, anti-inflammatory, and antithrombotic effects (Mineo et al 2006;Nofer et al 2004;Rye and Barter 2008;Tall et al 2008;Yuhanna et al 2001).…”
mentioning
confidence: 99%